India - Madyapur village - Punjab - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
These pictures were taken in connection to interviewing Dilbag Singh and Paramjit Sing, both farmers from Madyapur in India. They talk in the video series 'Farmer Testimonials' about the changes in the weather and how they are trying to adapt by for instance changing to hybrid seeds that require less water and pesticides.